On the need for a constitutionalism of continuity - Kwaśniewski, Jerzy (A thousand years of Poland's presence among the elite of European states, 2026)
The President of the Ordo Iuris Institute introduces the concept of "constitutionalism of continuity" — a doctrine premised on the idea that Poland's constitutional tradition is rooted in the coronation of Bolesław the Brave and encompasses successive forms of Polish statehood: Piast-era Poland, the Polish-Lithuanian Commonwealth, and the constitutions of the Second Polish Republic. His point of departure is the preamble to the 1997 Constitution of the Republic of Poland, which explicitly references "the best traditions of the First and Second Republics."Kwaśniewski draws an analogy between Polish constitutionalism of continuity and American originalism, arguing that just as originalism serves as a response to progressivism in the United States, constitutionalism of continuity can serve as Poland's answer to voluntarism and attempts to revise the constitutional order while bypassing democratic procedures. He emphasizes that where the constitution does not provide a definitive resolution, constitutional tradition should govern — in matters such as immigration, sovereignty, the relationship between domestic and international law, and judicial reform.The address concludes with a call to develop the doctrine of constitutionalism of continuity as a safeguard against the voluntarism threatening the foundations of the constitutional order. Kwaśniewski announces that the Ordo Iuris Institute will undertake research and scholarship initiatives in this area, invoking the words of Cardinal Stefan Wyszyński, who compared the nation to an ancient oak tree whose roots must never be torn out.